Place attachment in the Ex-situ poverty alleviation relocation: Evidence from different poverty alleviation migrant communities in Guizhou Province, China. (December 2021) - Zhu, Deming; Jia, Ziyu; Zhou, Zhengxu
Highlights: The levels of place attachment differ in the Ex-situ poverty alleviation relocation modes. Resettlement in cities and towns is more accessible in people-place relationship. The community support can effectively promote construction of place attachment. Individuals who face livelihood and families structure change require more attention. Abstract: The Ex-situ poverty alleviation relocation (ESPAR) program is an important policy initiative taken by the Chinese government to eliminate poverty. In a short time, a large number of migrants have moved to new communities for a better standard of living and opportunities for improving their condition. Place attachment is an important topic in migration, closely related to the people-place relationship and social stability. However, there are few relevant studies on the place attachment of poverty alleviation migrants (PAMs). To fill in this gap, we studied five new migrant communities in Anshun, Guizhou Province. We find significant differences between the three different resettlement modes (resettlement in original villages, resettlement in nearby townships, resettlement in cities and towns) in the place attachment level. The results of multiple linear regression models indicate that community support, such as basic infrastructures, social interaction, economy, and living environment significantly affect the construction of place attachment. Moreover, some sociodemographic characteristics and relocation factors also have significant impacts. Further policy recommendations including appropriate choice of resettlement modes, material and emotional guarantees, and comprehensive community support are put forward to improve the effectiveness of ESPAR.